Effect of intravenous amino acids on interdigestive antroduodenal motility and small bowel transit time. Issue 2 (1st February 1999) - Gielkens, H A J; van den Biggelaar, A; Vecht, J; Onkenhout, W; Lamers, C B H W; Masclee, A A M
Abstract : Background: Patients on total parenteral nutrition have an increased risk of developing gallstones because of gall bladder hypomotility. High dose amino acids may prevent biliary stasis by stimulating gall bladder emptying. Aims: To investigate whether intravenous amino acids also influence antroduodenal motility. Methods: Eight healthy volunteers received, on three separate occasions, intravenous saline (control), low dose amino acids (LDA), or high dose amino acids (HDA). Antroduodenal motility was recorded by perfusion manometry and duodenocaecal transit time (DCTT) using the lactulose breath hydrogen test. Results: DCTT was significantly prolonged during LDA and HDA treatment compared with control. The interdigestive motor pattern was maintained and migrating motor complex (MMC) cycle length was significantly reduced during HDA compared with control and LDA due to a significant reduction in phase II duration. Significantly fewer phase IIIs originated in the gastric antrum during LDA and HDA compared with control. Duodenal phase II motility index was significantly reduced during HDA, but not during LDA, compared with control. Conclusions: Separate intravenous infusion of high doses of amino acids in healthy volunteers: (1) modulates interdigestive antroduodenal motility; (2) shortens MMC cycle length due to a reduced duration of phase II with a lower contractile incidence both in the antrum and duodenum (phase I remains unchanged whereas the effect on phase III is diverse: in the antrum phase III is suppressed and in the duodenum the frequency is increased); and (3) prolongs interdigestive DCTT.